2007
DOI: 10.1186/1478-4491-5-24
|View full text |Cite
|
Sign up to set email alerts
|

Alumni survey of Masters of Public Health (MPH) training at the Hanoi School of Public Health

Abstract: Background: 1) To elicit the opinions of the Public Health alumni of the MPH program; 2) To assess the applicability of the knowledge and skills acquired; 3) To identify the frequency of the public health competencies that the alumni performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 2 publications
7
32
0
Order By: Relevance
“…Graduates felt the programme had helped them to enhance practical skills the most; a finding that is consistent with other studies on the impact of master's programmes of public health 9, 10, 11, 12, 13, leadership 14, 15, 16, 17 and primary care 18. Scores were somewhat lower for generic skills though.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Graduates felt the programme had helped them to enhance practical skills the most; a finding that is consistent with other studies on the impact of master's programmes of public health 9, 10, 11, 12, 13, leadership 14, 15, 16, 17 and primary care 18. Scores were somewhat lower for generic skills though.…”
Section: Discussionsupporting
confidence: 84%
“…Perceived skills and career progression have been used widely to assess the impact of postgraduate public health programmes because they provide valuable information for quality assurance and improvement 9, 10, 11, 12, 13, 14, 15, 16, 17, 18. In some cases, they are also useful for accountability, academic recognition (accreditation) and marketing purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Its current scope of practice is not with direct patient care. Similar to other countries, work is at local, regional and national levels [4–7], often in policy and leadership positions [8,9], in public institutions, in academia and research [5,10]. Specialists qualify through four-year university-based training progammes accredited by the HPCSA.…”
Section: Introductionmentioning
confidence: 99%
“…E-learning for healthcare has been strongly developed in other countries, as it can easily provide continuing medical education [5], but in Vietnam, it is only just beginning to be explored. In a previous needs assessment of healthcare workers, we identified a strong need for improved training in management skills and intellectual abilities [6][7][8]. Additionally, despite the healthcare professionals' expression of interest in lifelong continued professional education, we found that high workloads and lack of public appreciation towards public health and preventive medicine lead to a high rate of turnover and lack of motivation and desire to continue learning among healthcare workers.…”
Section: Introductionmentioning
confidence: 92%
“…Literature searches provided us with many skills to include, such as motivation and desire to learn [1,2] and interaction and collaboration skills [1][2][3][4]. We identified further specific skills through a review of our previous study on necessary skills for preventive medicine workers, which included management skills and intellectual abilities, as well as expected training outcomes for accredited public health and preventive medicine programs in Vietnam [6,7].…”
Section: Measures and Instrumentsmentioning
confidence: 99%